Growth, yield and nutrient content of mungbean (Vigna radiata L.) in response to INM in eastern Uttar Pradesh, India (Bangladesh Journal of Botany, 2018)
Significant improvement in LAI, number of trifoliate, SPAD value of green leaf chlorophyll, dry matter accumulation, yield, harvest index (%) and nutrient content of mungbean were recorded due to application of 75% RDF + 2.5 t/ha vermicompost (VC) + Rhizobium (Rh)+ phosphorus solublizing bacteria (PSB), followed by 100% RDF + 2.5 t/ha VC and 100% RDF + Rh + PSB. The highest seed yield of mungbean was obtained with the application of 75% RDF + 2.5 t/ha VC + Rh + PSB (12.34 q /ha) followed by 100% RDF + 2.5 t/ha VC (12.05 q /ha) and 100% RDF + Rh+ PSB (11.95 q /ha).